LINC00969 inhibits proliferation with metastasis of breast cancer by regulating phosphorylation of PI3K/AKT and ILP2 expression through HOXD8 - Xiaoyun Wen; Ya Hou; Liang Zhou; Xiansong Fang (PeerJ, 2023)
Background Breast cancer (BC) is a malignancy that is inadequately treated and poses a significant global health threat to females. The aberrant expression of long noncoding RNAs (lncRNAs) acts as a complex with a precise regulatory role in BC progression. LINC00969 has been linked to pyroptotic cell death and resistance to gefitinib in lung cancer cells. However, the precise function and regulatory mechanisms of LINC00969 in BC remain largely unexplored. Methods Cell proliferation, migration, and invasion of BC cells were evaluated using CCK-8 and Transwell assays. Western blotting was employed to analyze the protein expression levels of HOXD8, ILP2, PI3K, t-AKT, and p-AKT. Results LINC00969 was drastically reduced in BC tissues LINC00969 overexpression markedly suppressed proliferation, migration, and invasion, and blocked PI3K and p-AKT protein expression in MCF-7 cells. Activation of the PI3K/AKT pathway reversed the suppressive effect of LINC0096 overexpression on the proliferation, migration, and invasion of MCF-7 cells. Moreover, LINC00969 overexpression enhanced HOXD8 and blocked ILP2 protein expression in MCF-7 cells. In contrast, activating the PI3K/AKT pathway had no effect on HOXD8 and blocked ILP2 protein expression in MCF-7 cells overexpressing LINC00969. HOXD8 knockdown enhanced ILP2, PI3K, and p-AKT protein expression, and the proliferation, migration, and invasion of MCF-7 cells co-transfected with si-HOXD8 and ov-LINC00969. LINC00969 regulated HOXD8 via binding to miR-425-5p. Conclusion LINC00969 inhibits the proliferation and metastasis of BC cells by regulating PI3K/AKT phosphorylation through HOXD8/ILP2.